2000
DOI: 10.1007/bf03019663
|View full text |Cite
|
Sign up to set email alerts
|

The intubating LMA: a comparison of insertion techniques with conventional tracheal tubes

Abstract: Methods: After informed consent, 240 ASA I-II adults undergoing elective surgery participated in a randomized, single blind clinical trial to receive blind trachea intubation via ILMA with a conventional tracheal tube curved with normal (Normal group) or reversed (Reverse group) direction. More than three attempts at intubation was regarded as failure. The lowest oxygen saturation during intubation was recorded and postintubation sore throat and hoarseness were evaluated with verbal analog scales. Results:The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
36
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 19 publications
8
36
0
1
Order By: Relevance
“…These observations are confirmed in the study by Lu et al 1 They found that all of the failed intubating attempts occurred early in their study, within the first one hundred attempts. The single operator in this study was on the first part of the learning curve, being relatively unfamiliar with the technique and still perfecting this new skill.…”
supporting
confidence: 78%
See 4 more Smart Citations
“…These observations are confirmed in the study by Lu et al 1 They found that all of the failed intubating attempts occurred early in their study, within the first one hundred attempts. The single operator in this study was on the first part of the learning curve, being relatively unfamiliar with the technique and still perfecting this new skill.…”
supporting
confidence: 78%
“…8 Thus, experiential and life-centred learning are important to adult learners. This is confirmed by Lu et al 1 From this we see that new devices to manage the airway are practical solutions to everyday working life problems for these clinicians. In addition, we see these practitioners use the real life situations and experiences by which to learn these new techniques, especially through active participation.…”
supporting
confidence: 69%
See 3 more Smart Citations